The influence of cognitive reserve on ERP measures of selective visual attentional processing in older adults after mild traumatic brain injury - Sebastián A. Balart-Sánchez; Mayra Bittencourt; Seyedehzahra Jalili; Joukje van der Naalt; Natasha M. Maurits (PLoS ONE, 2025)
Objective Older adults have an increased risk of developing persistent cognitive complaints after mild traumatic brain injury (mTBI). Yet, studies exploring which factors protect older adults with mTBI from developing such complaints are rare. It has been suggested that one such factor may be cognitive reserve (CR), but it is unknown how CR influences cognition in this patient category. Here, we therefore study how CR influences brain processes during a task that taps into attention, an important cognitive function. Methods We studied 17 older adults (13 males, mean 68.18 (SD 5.08) years old) at the subacute stage after mTBI and 19 age- and CR-matched participants without mTBI; 9 males, mean 67.79 (SD 5.36) years old) performing a selective visual attentional processing task while recording EEG. The P2 brain event-related potential component was obtained by averaging over electrodes in the fronto-central region of interest and its amplitude and latency were derived as neural correlates of attentional processing. The inverse efficiency score (IES) was derived from accuracy and reaction times as a measure of performance. To investigate the effect of CR on performance and P2 component characteristics, three separate mixed model repeated measures analyses of covariance (RM-ANCOVA) were performed. Results Performance did not significantly differ across groups or task conditions, nor was it significantly influenced by CR. Main effects of CR illustrated that the P2 latency was delayed (p = .03) and the P2 amplitude increased (p = .02) with higher CR across groups. Furthermore, CR correlated positively with P2 latency in both groups (older adults without mTBI: r = .370, p = .005, older adults with mTBI: r = .287, p = 0.041), and with P2 amplitude in the older adults with mTBI (r = .595-.636, p<0.001-.011). We found no main or interaction effects of group or task condition on P2 characteristics. Conclusion Older adults with mTBI with higher CR employ more brain resources than older adults with mTBI with lower CR, accompanied by slower processing, suggesting that it may have resulted in similar performance at a selective visual attentional processing task. To better interpret these findings in the context of persistent complaints and establish that higher CR in these patients may result in better performance, our study needs to be repeated with more participants.